2019
DOI: 10.1080/09168451.2018.1527208
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1204 promotes ovarian squamous cell carcinoma growth by increasing glucose uptake

Abstract: MiR-1204 has been recently identified as an oncogenic miRNA in breast cancer. Our study aims to investigate the role of miR-1204 in ovarian squamous cell carcinoma. Expression of miR-1204 and glucose transporter 1 in ovarian biopsies and plasma of both OC patients and healthy controls was detected by qRT-PCR. Correlations between patients’ clinicopathological data were analyzed by Chi-square test. MiR-1204 overexpression OC cell lines were established. Expression of GLUT-1 protein was detected by western blot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…MiR-137 suppresses CXCL12 expression, inhibiting glioblastoma progression [22]. Interestingly, miR-1204 have been manifested to drive the progression of breast cancer and ovarian squamous cell carcinoma via regulating cell growth and EMT [24,39]. Nevertheless, the role of miR-1204 in GBM was poorly comprehended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-137 suppresses CXCL12 expression, inhibiting glioblastoma progression [22]. Interestingly, miR-1204 have been manifested to drive the progression of breast cancer and ovarian squamous cell carcinoma via regulating cell growth and EMT [24,39]. Nevertheless, the role of miR-1204 in GBM was poorly comprehended.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the oncogenic role of miR-1204 in some cancers has been validated. For instance, miR-1204 contributes to cell growth in ovarian squamous cell carcinoma via increasing glucose uptake [24]. MiR-1204 promotes epithelialmesenchymal transition (EMT) and metastasis in breast cancer by targeting VDR [25].…”
Section: Introductionmentioning
confidence: 99%
“…At present, few studies have been conducted in the investigation of hsa-miR-934 . For hsa-miR-1204 , Xu et al (43) revealed that hsa-miR-1204 expression was significantly correlated with tumour size. The expression levels of hsa-miR-1204 and glucose transporter-1 (GLUT-1) were significantly high in ovarian cancer (OC) patients (43).…”
Section: Discussionmentioning
confidence: 99%
“…For hsa-miR-1204 , Xu et al (43) revealed that hsa-miR-1204 expression was significantly correlated with tumour size. The expression levels of hsa-miR-1204 and glucose transporter-1 (GLUT-1) were significantly high in ovarian cancer (OC) patients (43). The expression levels of hsa-miR-1204 were positively correlated with the expression levels of GLUT-1 in OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of miR-1207-5p reduces the expression of signal transducers and activators of transcription (STAT6), thereby activates cyclin-dependent kinase inhibitor 1A (CDKN1A) and CDKN1B to regulate the cell cycle and promote tumor cell proliferation (49). In addition, the elevated expression of miR-1204 not only significantly increases glucose transporters 1 (GLUT-1) expression and glucose uptake but also suppresses the expression of pitx1 and Vitamin D (1,25- dihydroxy vitamin D3) receptor (VDR), which ultimately promotes cell proliferation, invasion, and metastasis (50, 51). In addition, miR-1205 downregulates the expression of the Egl-9 family hypoxia-inducible factor 3 (EGLN3) and promotes cell proliferation and cell cycle progression and inhibits hydrogen peroxide-induced apoptosis (52).…”
Section: Pvt1 Regulates Tumor Progression Through Encoding Mirnasmentioning
confidence: 99%